Mechanical properties of hybrid polypropylene composite reinforced with oil palm and coir fiber - Brian, Deng. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The study shows the reinforcement of natural fiber that is oil palm and coir to polypropylene composite. The main objectives of the project are to achieve the good combination of properties of hybrid oil palm EBF and coir as filler reinforced in polypropylene composite. The hybrid composite having polypropylene reinforced with coir and oil palm EBF fiber wil l give different result in mechanical properties of the composites compared to the coir or oil palm EBF fiber as filler as single filler in polypropylene composite. Thus in this study the effect of combine the coir and oil palm EFB to polypropylene matrix composite on the mechanical properties was investigated . In this study, the fiber loading is varies from 10%, 15%, 20%, 25% and 30% incorporated to the composite . The test is carried out to find the mechanica l properties of the composite. The test that con ducted was tensile test, flexural test and water absorption test. The test also carried in two state of fiber that is untreated fiber and treated fiber. The coupling agent used in this study is sodium periodate (NaIO 4 ) and sodium hydroxyl ( NaOH ) . The test show that the addition of fiber loading to composite did not improve the tensile strength of composite for treated or untreated fiber. For flexural test the addition of untreated fiber to composite did not improve the flexural properties but for treated fi ber the additional of fiber to composite improve it flexural strength. The water absorption test revealed that additional of untreated fiber improved water absorption but additional of treated fiber did not improved water absorption characteristic .